2022
DOI: 10.3390/cancers14246229
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the Age Discrepancy between Frailty-Based Biological Age and Expected Life Age in Patients with Urological Cancers

Abstract: Background: The estimation of biological age is challenging in patients with cancers. We aimed to investigate frailty-based biological ages using frailty-discriminant scores (FDS) and examined the effect of biological-expected life age discrepancy on the prognosis of patients with urological cancers. Methods: We retrospectively evaluated frailty in 1035 patients having urological cancers. Their frailty-based biological age was then defined by the FDS, which is a comprehensive frailty assessment tool, using 179… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Our previous studies have suggested that the degree of frailty increases at age 80 or older, which may be useful as a convenient cutoff for Japanese patients. 14…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies have suggested that the degree of frailty increases at age 80 or older, which may be useful as a convenient cutoff for Japanese patients. 14…”
Section: Discussionmentioning
confidence: 99%
“…We selected the age of 80 as a threshold because it is an important cutoff value for determining the indication for surgery and the intensity of treatment. Our previous studies have suggested that the degree of frailty increases at age 80 or older, which may be useful as a convenient cutoff for Japanese patients 14 …”
Section: Methodsmentioning
confidence: 99%
“…Within the context of onconephrology, there have been recommendations to utilize a ‘simple value score’ based on age to determine the extent of frailty. A recently published study by Togashi and colleagues [ 109 ] investigated frailty-based biological ages using frailty-discriminant scores (FDS) and examined the effect of biological–expected life age discrepancy on the prognosis of patients with urological cancers. The FDS is a comprehensive frailty assessment tool including eGFR as a frailty parameter [ 110 ].…”
Section: Recommendations For a Summarized Frailty Assessment Tool In ...mentioning
confidence: 99%